2021
DOI: 10.3389/fcimb.2021.732613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helicobacter pylori Infection on the Oral Microbiota of Reflux Esophagitis Patients

Abstract: The human oral microbiota plays a vital role in maintaining metabolic homeostasis. To explore the relationship between Helicobacter pylori (Hp) and reflux esophagitis, we collected 86 saliva samples from reflux esophagitis patients (RE group) and 106 saliva samples from healthy people (C group) for a high-throughput sequencing comparison. No difference in alpha diversity was detected between the RE and the C groups, but beta diversity of the RE group was higher than the C group. Bacteroidetes was more abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Although there were obvious individual differences in abundance values, the overall abundance showed obvious diurnal abundance changes ( Takayasu et al., 2017 ), which were consistent with our results. Studies had found that oral Bacteroidetes was related to type 2 diabetes mellitus ( Chen et al., 2020 ), inflammatory bowel disease (IBD) ( Said et al., 2014 ), reflux esophagitis ( Liang et al., 2021 ), etc. The findings of this study may provide some references for establishing the best microflora therapeutic intervention time for these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were obvious individual differences in abundance values, the overall abundance showed obvious diurnal abundance changes ( Takayasu et al., 2017 ), which were consistent with our results. Studies had found that oral Bacteroidetes was related to type 2 diabetes mellitus ( Chen et al., 2020 ), inflammatory bowel disease (IBD) ( Said et al., 2014 ), reflux esophagitis ( Liang et al., 2021 ), etc. The findings of this study may provide some references for establishing the best microflora therapeutic intervention time for these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We used linear discriminant analysis [ 30 ] effect size (LEfSe) methods to identify microbial taxa that differed significantly between groups (LDA score ≥ 2) [ 31 ]. Details of our microbial network construction methods were described previously [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…As the samples collected for evaluation varied among different studies, the sequencing results of microbiota composition may differ from each other. Our study showed that saliva and fecal samples were most utilized to analyze oral and gut microbiota 12,34 . Gastric mucosa samples, such as antrum samples and corpus samples, accounted for more than 90% of the studies, which was more commonly used compared with fluid samples 10 …”
Section: Discussionmentioning
confidence: 92%
“…Our study showed that saliva and fecal samples were most utilized to analyze oral and gut microbiota. 12,34 Gastric mucosa samples, such as antrum samples and corpus samples, accounted for more than 90% of the studies, which was more commonly used compared with fluid samples. 10 Our study has certain limitations.…”
Section: Discussionmentioning
confidence: 99%